Hepatitis disease prediction using neutral network - Basbas, Ma. Cristina A.; Borlon, Jasmine Belinda C.; Dandan, Aliyah Jane P. 4 0 16; 5 (2024)
u
Undergraduate Thesis: (Bachelor of Science in Information Technology) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2